Development of new SSR markers for homoeologous WFZP loci based on the study of structure and location of microsatellites in gene-rich regions of chromosomes 2AS , 2BS, 2DS - O. B. Dobrovolskaya; C. Pont; Yu. L. Orlov; J. Salse (Вавиловский журнал генетики и селекции, 2015)
Microsatellites, or simple sequence repeats (SSRs), are ubiquitous in genomes of eukaryotes, including plant genomes. The structure and location of SSR loci determine their potential as molecular genetic markers and may have impact on the potential function of microsatellites in important biological processes. Identification and study of the distribution of SSR loci in gene-rich regions of the bread wheat genome and development of novel SSR markers based on these data are of practical interest, being important for the study of bread wheat genome organization. Bread wheat BACclone sequences containing homoeologous WFZP genes that control spikelet development served as the base for the identification and localization of SSR loci in generich regions of chromosomes 2AS, 2BS, and 2DS. It was found that di- and trinucleotide motifs were predominant. The most common dinucleotide motifs were AG and GA/TC. They were distributed in noncoding regions of genes, transposable elements (TEs) and unannotated sequences. Most identified trinucleotide motifs were associated with transposable elements. Homoeologous SSR loci were found in either genes or unannotated sequences. Comparison of these loci showed that the divergence in their structure was caused both by changes in repeat number and nucleotide substitutions. New SSR markers were developed and mapped. On the genetic maps of chromosomes 2A, 2B и 2D, they collocated with the WFZP-A-B-D genes. Thus, they can be used for gene tagging in molecular research and in marker-assisted selection.